INTRODUCTION OF CaO FROM OYSTER AND ECOENZIM FOR MAKING VIRGIN COCONUT OIL - Vanny M.A. Tiwow; Paulus Hengky Abram; Sri Hastuti V. Pulukadang; Yinangsih Safitri (Journal Of Social Science (JoSS), 2024)
Virgin coconut oil (VCO) is a form of processed coconut meat that is pure and free from Free fatty acids. VCO is widely known as cooking oil, cosmetics, antioxidants and health benefits, because the ingredients are high in lauric acid. The purpose of this research are to produce VCO by utilizing CaO from oyster and Eco-enzyme for de-emulsifying protein to separated oil from water and to measure both the decreasing of free fatty acid number and the decreased peroxide number as a parameter of the quality of the resulting VCO. Applications of CaO and Eco-enzyme ferry simple just mix both each 0.2 gr, 0.4 gr, 0.6 gr. of CaO and 0.2 mL., 0.4mL., 0.6 mL. of Eco-enzyme with 100 mL. coconut milk stirrer it. After treatments, it can be concluded that: separation of water from oil in the manufacture of VCO from coconut milk can occur using CaO and using Eco-enzyme It means that de-emulsification of protein in coconut milk is working well. To determine the quality of production VCO from CaO de-emulsification found 50.00 % the decreasing of Free Fatty Acid number and the decreasing of peroxide number is 28.57 %. From eco-enzyme de-emulsification the results are 55.55 %, the decrease of the acid number (DAN) and 57.14% the decrease of the peroxide number (DPN).